IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH TOTAL PHYSICAL RESPONSE METHOD AT SEVENTH GRADE STUDENTS OF MTS HIDAYATUSSALAM BANDAR KHALIPAH - Nurhalimah Lbs, Ika (BRIGHT VISION Journal of Language and Education, 2022)
This research was conducted to describe the improvement of students’ vocabulary mastery through Total Physical Response method at seventh grade students of MTs Hidayatussalam  in  2020/2021  academic  year.  The  research  design  used  was  Classroom Action Research (CAR). The participants of this research consisted of 25 students of VII-1. In this research, the English teacher of MTs Hidayatussalam act as the observer. The research conducted in two cycles, each cycle consisted of two meetings. The research was carried out through four steps; planning, acting, observing, and reflecting. There are two kinds of data, qualitative and quantitative data. The qualitative data were taken from by the interview and observation sheet result, diary notes, and documentation. Meanwhile, quantitative data were obtained from the students' score of vocabulary test, include pre-test, post-test I, and post-test II.  The  result  of  data  analysis  indicated  that  there  was  the  improvement  of  students’ vocabulary mastery through Total Physical Response method. The students achieved better score in every cycle. The minimum passing grade (KKM) in this school was 75. From the data analyzing, it showed the mean of the pre-test was 56,3, the mean of post test I was 79,4, and the mean of post test II was 83,2. It can be seen that the mean improved in each cycle. The percentage of students’ score also increased. In the pre-test, there were just 5 students who achieved score ≥75 or passed the test (20%). In the post-test I, 17 students successfully passed the test (68%). From the pre test to post test I the increase was 48%. In the post-test II, there were 23 students who passed the test (92%). The increase from the post test I was 24%. The percentage of students’ score improved and getting higher in every cycle. In conclusion, the students’ vocabulary mastery improved by the implementation of the TPR method. Based on  qualitative  data  analysis,  it  showed  that  the  students  give  positive  responses  to  this research. The students enjoy and enthusiast in teaching learning activity. It was found that the implementation of Total Physical Response method can make students easier to memorize the vocabulary, and it makes them can improve their vocabulary mastery. In other words, the Total Physical Response method effective to improve the students’ vocabulary mastery.